Sensitivity of Sesamum Indicum L. to Soil Moisture Stress at Different Developmental Stages - Vyas, S P; Garg, B K; Kathju, S; Lahiri, A N (Annals of Arid Zone, 2016)
Results relate performance alteration in Sesamum indicum L. due to water stress at different stages of growth. Stress induced maximum adverse effects at 30 and 40 days from sowing when the grand period of growth and flowering just commenced. Favourable moisture condition at subsequent stages did not alleviate this irreversible damage although growth, flowering and fruiting continued due to the indeterminate flowering habit of the crop. The yield reduction seemed to be linked with reduction in seed number per capsule and lOOO-seed weight. Causes of irreversible changes at the critical stage could not be ascertained froin the study of metabolites, such as, proline, free aminoacids, soluble protein, reducing sugars and starch, as well as activities of enzymes like nitrate reductase, alkaline pyrophosphatase and peroxidase in the leaves, at wilting and recovery of 30 days’ old plants. Drought mediated reduction in seed yield was associated with increase in oil content and with indications of decline in protein and carbohydrates.